(untitled) (Comparative Professional Pedagogy, 2024)
The article explores the organizational principles underpinning the professional development of choreography educators in the United States. It clarifies the requirements for professional competence and addresses the needs of choreography teachers within the context of contemporary trends in choreography and choreographic education. These trends include the integration of digital technologies in art pedagogy, the application of interdisciplinary approaches in training, a focus on inclusivity and cultural diversity, the enhancement of professional standards and certification processes, and the introduction of online education. Such trends reflect the rapid evolution and modern challenges in choreographic-pedagogical education in the U.S., aiming to cultivate competent professionals in dance pedagogy. The author analyzes the roles of professional organizations in promoting choreographic education and supporting the professional development of choreography educators. It characterizes various programs (such as WeTeachNYC) and forms of professional development, including master classes, workshops, intensive training sessions, internships, participation in dance projects and performances, self-education, and attendance of professional conferences and seminars. Special attention is paid to certification programs, such as the "Certificate in Dance Education" (organized by the National Organization of Dance Education), the "Certificate Programs" (by the Broadway Dance Center), the "Certificate in Dance" (by the Juilliard School), and the "Certificate Programs" (by the Festival of American Dance). The study clarifies motivators and methods for encouraging choreography educators’ professional development, substantiating that the concept encompasses a range of approaches and strategies aimed at enhancing skills, knowledge, and professional opportunities in dance teaching. It concludes that American society requires choreography educators who possess not only high levels of professional knowledge and creative potential but also the psychological readiness for continuous improvement, the ability to evaluate new trends in choreographic art, and the ability to adapt swiftly to these changes.